EKSPRESI MATRIKS METALLOPROTEINASE-8 DAN INTERLEUKIN-8 PADA KERUSAKAN JARINGAN PERIAPIKAL AKIBAT INDUKSI BAKTERI ENTEROCOCCUS FAECALIS - Tamara Yuanita; Tantri Wismayaning Radito; Dian Agustin wahjuningrum; R. Roulianto (Universitas Airlangga, 2017)
Background. The main etiology of endodontic treatment failure is caused by bacteries that stay in the root canal. E.faecalis is a bactery that is found as an etiology of endodontic treatment failure. Cell wall of this bacteria is containing Lipoteichoic acid (LTA). LTA can penetrate into the periradicular tissue, act as endotoxin in host and cause periradicular inflammation and destruction. It occurs due to the capability of IL-8 to enhance the inflamation reaction and MMP-8 to stop the collagen formation. The ability of enterococcus faecalis in enhancing inflamation process cause host can not reach the homeostasis phase and performing an even bigger tissue damage. Purpose. The aim of this study is to know about the expression of MMP-8 and IL-8 during the periapical tissue damage due to induction of E.faecalis. Method. This study used laboratory experimental with the post test only control group design. A total of 54 male rats were randomly divided into 2 main groups, which each main group had 3 subgroups. Group A (control) : every tooth was induced only by sterile BHIb. Group A had 3 subgroups (A Control day 3, 10, and 21), group B : every tooth was induced by 10 μl BHI-b E.faecalis ATCC212(106 CFU), it was contained 3 sub groups (B day 3,10, and 21). The animals were sacrificed based on their days scheduled group and prepared for histological examination of tissue damage, then we did the immunohistochemistry followed by calculation on the light microscope. Result. The analysis revealed that the expression of MMP-8 and IL-8 increased significantly in group B when E.faecalis was induced. Conclusion. From this study we know that the expression of MMP-8 and IL-8 are increasing during the periapical tissue damage that induced by E.faecalis.